2016
DOI: 10.1007/s00464-016-4892-z
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted versus laparoscopic-assisted surgery for colorectal cancer: a meta-analysis

Abstract: Based on this meta-analysis, RACS appears to be a promising surgical approach with its safety and efficacy comparable to that of LACS in patients undergoing colorectal surgery. Further studies are required to evaluate the long-term cost-efficiency as well as the functional and oncologic outcomes of RACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 64 publications
7
34
0
Order By: Relevance
“…One of the most updated meta-analyses that reviewed 24 studies between January 2010 and October 2015 concluded that the conversion rates, estimated blood loss, and length of hospital stay were significantly lower in robotic surgery. 20 The operative times and total costs were similar to laparoscopy, and there was no significant difference in complication rates and oncological outcomes. The publications by Xiong et al and Wang et al reported superior oncological outcomes in favor of robotics, with CRM positivity rates of 2.74% versus 5.78% for robotics and laparoscopy, respectively.…”
Section: Use Of the XI In Tmementioning
confidence: 74%
See 1 more Smart Citation
“…One of the most updated meta-analyses that reviewed 24 studies between January 2010 and October 2015 concluded that the conversion rates, estimated blood loss, and length of hospital stay were significantly lower in robotic surgery. 20 The operative times and total costs were similar to laparoscopy, and there was no significant difference in complication rates and oncological outcomes. The publications by Xiong et al and Wang et al reported superior oncological outcomes in favor of robotics, with CRM positivity rates of 2.74% versus 5.78% for robotics and laparoscopy, respectively.…”
Section: Use Of the XI In Tmementioning
confidence: 74%
“…19 Of the 24 studies included in the meta-analysis by Zhang et al, 17 were retrospective, and only the two by Jiménez-Rodríguez et al and Park et al were randomized trials. [20][21][22] All seven articles in the 2014 publication by Xu et al were included in a 2015 publication by Chang et al, and some of these articles also contributed to half of the meta-analysis by Zarak et al 11,12,[22][23][24][25][26] Between 2014 and 2016, three different journals separately published meta-analyses on robotic versus laparoscopic rectal cancer surgery -all included the same eight studies and 1229 patients. [27][28][29] Two of these publications were authored by the same group.…”
mentioning
confidence: 99%
“…Robotic surgery for colorectal cancer has been widely accepted over the past decade. High-quality evidence such as RCTs and meta-analysis has suggested that robotic surgery can achieve oncological safety compared to laparoscopy with lower conversion rate and faster recovery [ 23 , 24 ]. However, it is still not well explored whether the advantages of robotic surgery can translate into better urogenital function after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis assessed 24 studies, including two RCTs, with 3318 patients, compared robotic versus laparoscopic surgery for colorectal cancer. 28 The robotic group had significantly lower rates of conversion. There was no difference in postoperative complication rates, distal resection margins, or costs.…”
Section: Robotic Anastomosis After Right Colectomymentioning
confidence: 95%